Strategies for the Modification of Vaccinia Virus towards a Better Vaccine Vector - Hao Sun; Xinwen Chen; Yun Wang (Zoonoses, 2025)
Vaccinia virus (VACV) confers cross-protective immunity against variola virus, the causative agent of smallpox, and has therefore been extensively exploited as a preventive vaccine. Despite the global eradication of smallpox in the 1980s, research efforts involving VACV have continued due to the potential threat of variola virus being used as a bioweapon, which poses grave risks to human health. VACV has emerged as a promising viral vector for vaccine development beyond the traditional application of VACV in smallpox prophylaxis, which has been attributed to its capacity for efficient foreign gene expression. Leveraging strategies, such as serial passage in alternative hosts and genetic engineering techniques, have generated highly attenuated VACV vaccine vectors by deleting specific viral genes, most notably those encoding immunomodulatory proteins. The recent emergence of pathogenic orthopoxvirus outbreaks, exemplified by monkeypox, has reignited scientific interest in VACV research. This review delineates the commonly targeted viral genes for attenuation during VACV vector modification and provides an overview of the progress in VACV-vectored vaccine development.